2020
DOI: 10.1002/ana.25717
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic Multiple Sclerosis Risk and Population‐Based Childhood Brain Imaging

Abstract: Objective: Multiple sclerosis (MS) is a neurological disease with a substantial genetic component and immune-mediated neurodegeneration. Patients with MS show structural brain differences relative to individuals without MS, including smaller regional volumes and alterations in white matter (WM) microstructure. Whether genetic risk for MS is associated with brain structure during early neurodevelopment remains unclear. In this study, we explore the association between MS polygenic risk scores (PRS) and brain im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Recent studies demonstrated that polygenetic risk scores are informative measures of risk in MS and other autoimmune diseases [40][41][42][43] . Cell-specific risk scores incorporating variants based on 3D chromatin interaction profiles also show statistically significant association with risk, suggesting that diseaseassociated variants mediate susceptibility to a large degree through chromatin interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that polygenetic risk scores are informative measures of risk in MS and other autoimmune diseases [40][41][42][43] . Cell-specific risk scores incorporating variants based on 3D chromatin interaction profiles also show statistically significant association with risk, suggesting that diseaseassociated variants mediate susceptibility to a large degree through chromatin interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Traits with worse than expected performance even when thousands of cases are available include autism spectrum disorder 3 , heart failure 4,5 , major depressive disorder (MDD) 6,7 , and some addictions [8][9][10][11] . Increasing sample size to increase statistical power for discovery is not always practical, as encountered for rare diseases 12 , expensive phenotyping 13 , phenotypic heterogeneity 14 , hard-to-reach or socially disadvantaged populations 15 , and population isolates 16 . Our ability to discover trait-associated loci that are ancestryspecific or subject to gene-environment interaction lags in a field where the overwhelming majority of GWAS samples are of European ancestry 17 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we imputed the genetic data using data from 1000 Genomes (Phase I, version 3) [ 20 ]. Quality control measures performed on the genetic data, a detailed description of the imputation method, and the calculation of principal components (PCs) have been published previously [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have shown that children from a population‐based study with a high polygenic risk for MS show alterations in the white matter microstructure of the brain and in the T‐cell compartment of the immune system, which hints at early susceptibility factors for the disease process emerging in childhood [ 9 , 10 ]. The importance of B cells and the interaction between B and T cells in MS pathophysiology warrant additional investigation of the influence of genetic risk for MS on the B‐cell compartment and how this influences the distribution of naive and memory B cells during childhood [ 11 ].…”
Section: Introductionmentioning
confidence: 99%